Competency of Human Resources as Part of Performance Assessment in the Effort to Increase Organizational Performance - Lisda L. Asi (AIBPM Publisher, 2018)
Personel competencies drive from the value and core competencies of the organization.Personalhave unique character and difference competencies is important asset for organization, and the personelcompeties are very much conneted to orgnationalcompoties. So, when we appraise organization performance, we must appraise personel competies personel performance . Competency-based to be directed towards the esthabilishment of a common language/vocabulary between organizational expectations and individuals need to achieve optimal performance organization. To devlopmentpersonel based, human considerateas unique person and treat itself,it make high creative and innovative person. Competencies – based is focus on human resources, to apply management development programseffectifely .Compotencies based has a concentration on what managers actually do, rather then on assumptions abaout what managers do. Althoungh competencies – based has lacks, many organization has been success to achieve optimal performance by competencies based. Keywords: Compotency, Human resources, performance, competencies.